Immunotherapy for Head and Neck Cancer: A Paradigm Shift From Induction Chemotherapy to Neoadjuvant Immunotherapy - Shibata, Hirofumi; Saito, Shin; Uppaluri, Ravindra (Frontiers in Oncology, 2021)
Neoadjuvant immunotherapy has the potential to enhance clinical outcomes by increasing anti-tumor immune responses in the presence of abundant tumor-derived antigen in an immune microenvironment that has not been exposed to previous therapy. The current mainstay of advanced head and neck squamous cell carcinoma (HNSCC) treatment remains surgery and radiotherapy with/without conventional chemotherapy. Despite this multi-modality treatment, advanced human papillomavirus (HPV)-negative HNSCC shows poor prognosis. Treatment intensification with neoadjuvant (induction) chemotherapies with platinum drugs are insufficient to significantly prolong overall survival. Although only 15-20% of patients benefit, immunotherapies have been approved and widely used for recurrent and metastatic HNSCC. These successes have led to checkpoint blockade therapies being testing in earlier treatment settings. Recent clinical trials of neoadjuvant immunotherapy show promising results and this methodology has the potential to change the treatment algorithm of HNSCC. This overview examines the treatment history of neoadjuvant approaches for HNSCC, and especially focuses on the recent topics of neoadjuvant immunotherapy for HNSCC.